On Theological, Philosophical and Sociological Themes - Davide Ceccoli Crimi (Academicus International Scientific Journal)

(untitled)
The article is the report of an attempt to connect Manlio Sgalambro, philosopher and theologian, standard-bearer of “negative theology”, with Luigi Moraldi, hermeneutist and exegete of the “gnostic texts”, who was part of the international team of translation of the Nag-Hammadi manuscripts. The meeting did not take place, but it remains a correspondence of great interest both for the contents it deals with and for the specific approaches of the two great intellectuals on the subject that, even in the present of this 21st century, continues to be overwhelming for the general system of knowledge.